2016
DOI: 10.1111/iju.13261
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary rates of pathological features and mortality for adenocarcinoma of the urinary bladder in the USA

Abstract: In bladder cancer, adenocarcinoma presents at higher stages than urothelial carcinoma. However, cancer-specific mortality rates do not differ. A more unfavorable stage at diagnosis and higher cancer-specific mortality apply to the signet-ring cell variant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…The incidence and mortality rates of BLCA patients are higher in elderly people. 40 The higher mortality rate in the elderly can be explained by several reasons. Elderly BLCA patients have increased genetic aberrations and tend to exhibit a poor-differentiated histology and a more aggressive phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence and mortality rates of BLCA patients are higher in elderly people. 40 The higher mortality rate in the elderly can be explained by several reasons. Elderly BLCA patients have increased genetic aberrations and tend to exhibit a poor-differentiated histology and a more aggressive phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Sarcomatoid-variant urothelial carcinoma is an uncommon histological variant of urothelial carcinoma [ 4 ]. The majority of sarcomatoid-variant urothelial carcinomas is found in the bladder, accounting for less than 1.0% of all bladder cancer cases [ 5 , 6 ]. Generally, sarcomatoid carcinoma is a biphasic malignant tumor exhibiting morphological and/or immunohistochemical evidence of epithelial and mesenchymal differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed that these histological variants resulted in worse pathological features and/or survival outcomes, relative to UCUB. [2][3][4][5][6][7][8] NCCN guideline recommendations for treatment of non-UCUB vary according to histological variants. 9 RC with neoadjuvant CHT is recommended for NC patients.…”
Section: Introductionmentioning
confidence: 99%